Influence of oil leakage in the pressure and flow rate behaviors in pipeline - de Sousa, Carolina Andrade; Romero, Oldrich Joel (Latin American Journal of Energy Research, 2021)
Pipelines are highly used in the oil industry for the transportation of oil, natural gas and products from refineries. One of the main areas of study in pipeline engineering is the flow guarantee. This paper describes the steady state dynamics behavior of oil flow in a pipeline with the presence of a leak. The mathematical and numerical modeling of a single-phase flow in a one meter pipeline with a diameter of 0.15 m in an onshore environment. Three different sizes of leaks are studied based on fluid dynamics simulations using the ANSYS FLUENT® 15.0 commercial software. The interest of this paper is to evaluate the influence of leakage on the pressure, velocity fields and flow rates in a 3D section of pipe in order to identify the influence of the perturbation in these parameters. The results obtained is interpreted in the CFD- Post that is included in the software package. Thus, this work intends to contribute to the development of operations tools in oil and gas industry.